A Formal Exchange Reaction between Ketones and Vinyl Ethers with Solid Catalysts - Mingueza-Verdejo, Paloma; Cerón-Carrasco, Jose Pedro; Oliver-Meseguer, Judit; Leyva-Pérez, Antonio (Synthesis, 2023)
The formal exchange of functional groups in internal positions of two different molecules is of interest in synthetic chemistry, as a simple retrosynthetic strategy. Here the formal exchange reaction between internal α-methylene ketones and vinyl ethers, retaining the original C–O bonds is presented. This process offers a new route for the synthesis of vinyl ethers in one step from ketones, including 1,3-diketones, under mild reaction conditions. Besides, the reaction is catalyzed by reusable cheap solids and can be carried out in flow for 20 days without signs of catalyst depletion. Combined experimental and computational mechanistic studies unveil the key role of carbonyl–enol equilibria.
Keywords: solid catalyst; vinyl ether; ketone; exchange reaction; reaction in flow